Using Apps to improve service delivery in Malaysian hotels: guests' and employees' rationales - Selke, Raimond; Ang, Lay Hoon; Schaar, Torsten (Tourism Educators Association of Malaysia, 2015)
The paper considers a looming crisis for the important Malaysian tourism sector, namely, the lack of communication skills of hotel staff. There are a growing number of overseas visitors coming to this popular destination, yet hotel staff, polite as they may be, are increasingly unable to communicate effectively with them. Whilst this is acknowledged as being a worldwide phenomenon that ultimately leads to customer dissatisfaction, the authors believe it is exacerbated in Malaysia by governmental education policies that may seem biased in favour of Bahasa Malaysia as the medium of instruction. In addition to other internal and external factors that currently put pressure on the hotel industry, Malaysia, unlike many other countries, permits foreigners to work in the hotel industry, and many of them arrive with a poor command of English. Hence the main objectives of the study are to improve understanding of both the communication problems within the hotel industry as well as the sentiment associated with using a technology based solution. The authors linked their aims to research questions which were formulated for both hotel staff and overseas visitors, and evidence was subsequently derived from the analysis of the responses received. As a solution to the communication problem, it is proposed that hotels should provide staff with hotel centred training in both English for Specific Purposes (ESP) as well as other key languages that are spoken by overseas visitors who are non-English speakers. In addition, a technological solution, in the form of an appropriate ‘App’, is proposed. Such an App could be used in a variety of ways to significantly improve communication, and ultimately, guest satisfaction.